2023
DOI: 10.1002/anie.202302595
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐layer 3D Chirality and Double‐Helical Assembly in a Copper Nanocluster with a Triple‐Helical Cu15 Core

Abstract: Conceptually mimicking biomolecules' ability to construct multiple-helical aggregates with emergent properties and functions remains a long-standing challenge. Here we report an atom-precise 18-copper nanocluster (NC), Cu 18 H(PET) 14 (TPP) 6 (NCS) 3 (Cu 18 H) which contains a pseudo D 3 -symmetrical triple-helical Cu 15 core. Structurally, Cu 18 H may be also viewed as sandwich type of sulfur-bridged chiral copper cluster units [Cu 6 À Cu 6 À Cu 6 ], endowing three-layered 3D chirality. More importantly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Dong et al recently reported Cu 18 H(PET) 14 (PPh 3 ) 6 (isothiocyanate) 3 NC and its effectivity toward the reduction of ferricyanide. 67 The structure is visualized as a conventional core–shell structure which consists of a triple-helical Cu 15 core and [(Cu isothiocyanate) 3 (PET) 14 (PPh 3 ) 6 ] shell. They observed that the clustered NCs display photoluminescence emission in the deep-red spectrum and, in addition, exhibit impressive efficacy in catalyzing electron transfer reactions.…”
Section: Effect Of Cu Ncs In Chemical Catalysismentioning
confidence: 99%
“…Dong et al recently reported Cu 18 H(PET) 14 (PPh 3 ) 6 (isothiocyanate) 3 NC and its effectivity toward the reduction of ferricyanide. 67 The structure is visualized as a conventional core–shell structure which consists of a triple-helical Cu 15 core and [(Cu isothiocyanate) 3 (PET) 14 (PPh 3 ) 6 ] shell. They observed that the clustered NCs display photoluminescence emission in the deep-red spectrum and, in addition, exhibit impressive efficacy in catalyzing electron transfer reactions.…”
Section: Effect Of Cu Ncs In Chemical Catalysismentioning
confidence: 99%
“…This is commonly found in the secondary structure of biological macromolecules, , such as the conversion of l -amino acids into proteins with α-helical DNA or a d -nucleotide into P -helical DNA . In the synthesis system, chemists also realize the biomimetic assembly from the small molecules to secondary structures through various noncovalent interactions, , such as π–π interactions, , hydrogen bonds, , and other noncovalent interactions. This process results in chirality transfer from the microscale to the mesoscale. The chiral secondary structures (like helices) had a mesochirality similar to the screw dislocations, which are considered crucial in the chiral Te nanocrystals . Therefore, based on the appropriate chiral secondary structure assembly, it is anticipated that a continuous chiral transfer can be achieved, progressing from the microscale to the mesoscale, and ultimately to the macroscale.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lack of precise structural information about the NPs, it remains a great challenge to accurately identify the assembled array of synthetic NPs. Some nanoclusters can be used as well-defined nanobuilding blocks to assemble into double-stranded helices. Endowing chiral clusters or chiral building blocks is a prerequisite for the construction of homohelical assemblies. However, the synthesis of chiral clusters is still a challenge. , …”
Section: Introductionmentioning
confidence: 99%